Displacement behaviour is associated with reduced stress levels among men but not women - Mohiyeddini, Changiz; Bauer, Stephanie; Semple, Stuart (PLOS ONE, 2013)
Sex differences in the ability to cope with stress may contribute to the higher prevalence of stress-related disorders among women compared to men. We recently provided evidence that displacement behaviour - activities such as scratching and face touching - represents an important strategy for coping with stressful situations: in a healthy population of men, displacement behaviour during a social stress test attenuated the relationship between anxiety experienced prior to this test, and the subsequent self-reported experience of stress. Here, we extend this work to look at physiological and cognitive (in addition to self-reported) measures of stress, and study both men and women in order to investigate whether sex moderates the link between displacement behaviour and the response to stress. In a healthy study population, we quantified displacement behaviour, heart rate and cognitive performance during the Trier Social Stress Test, and used self-report questionnaires to assess the experience of stress afterwards. Men engaged in displacement behaviour about twice as often as women, and subsequently reported lower levels of stress. Bivariate correlations revealed that for men, higher rates of displacement behaviour were associated with decreased self-reported stress, fewer mistakes in the cognitive task and a trend towards lower heart rate; no relationships between displacement behaviour and stress measures were found for women. Moreover, moderation analyses revealed that high rates of displacement behaviour were associated with lower stress levels in men but not in women, and that high displacement behaviour rates were associated with poorer cognitive performance in women, but not men. These results point to an important sex difference in coping strategies, and highlight new avenues for research into sex biases in stress-related disorders.
Gesehen am 25.05.2021